Chatting with the author. On the Subject of an Essay on Camilo Torres and the Theology of Liberation - Umaña-Vargas, Daniel (2021)
As I approach the text presented by Samuel Silva Gotay on the legacy of Camilo Torres to Liberation Theology, I do not do so from an unexplored ground. In a way, I recall those days when a great teacher, Juan Stam, spoke to me of new realities. And I can only feel, think, relate that extraordinary Colombian leader, Camilo Torres, out of my own experience with the teachings of Juan Stam, another great Latin Americanist thinker.